An Algorithm to perform Sentiment Analysis of web reviews using C++ - Rajput, JE; Patil, MB (International Journal of Computer Sciences and Engineering, 2020)
Natural Language processing is one of the leading inventions in computer science. Sentiment is one of the sciences in NLP to perform web analysis. Sentiment analysis is opinion or review expressed by someone about something on web. As now a day’s people are depending trusting on online services so the importance of a review is going higher. For selecting a service or product, they need to go through thousands of reviews to understand a service or product quality. They can take proper decision based on these results of classification. Thus, considering the needs and developing attitude in web data mining and increasing dependency of users on reviews. Here we proposed a method and algorithm to classify the data of web reviews. Sentiment analysis is the process to classify positive, negative and neutral reviews and obtain output values that represents how many positive, negative and neutral reviews sentiment expressed. This paper refers a sentence level sentiment analysis.